Penambahan kelapa (Cocos nucifera) dan kacang tolo (Vigna unguiculata) terhadap nilai indeks glikemik singkong (Manihot utilissima) - Rini Astuti; Heni Hendriyani; Muflihah Isnawati (Jurnal Gizi Klinik Indonesia, 2013)
Backgound: The glycemic index (GI) is a notion that defences the glycaemic potency of foods. Foods with low GI will be digested and turned into glucose gradually and slowly. As a result blood glucose peak will not be so high and its fluctuation relatively in short time. Although cassava is a good source of carbohydrate, it has a high GI and low protein. Its GI factor needs to be reduced by any efforts to make it a healthy alternative food in spite of rice.Objective: To analize the effect of adding coconut and black-eyed pea to the GI factor of cassava.Method: The study used experimental observation design. There were three groups of treatment with 9 persons in each goup. After fasting for 10 hours, blood glucose were tested and 50 g of true glucose were given. Blood glucose of the subjects were tested again after 30, 60, 90 and 120 minutes giving true glucose. Next on the seventh day, they were given boiled cassava, cassava with coconut (sawut) and cassava with black-eyed pea (gintul). After which their blood glucose were also tested. Results: GI factor of steam cassava, shredded cassava and shredded cassava with black-eyed pea (gintul) was 100,40; 70,90; and 61,88; respectively. There was a significant difference of GI level between three products (p=0,031). Conclusion: Food processing by adding coconut and black-eyed pea has effect in reducing the GI level of cassava.